Marquess of Queensberry : Wilde's nemesis - Stratmann, Linda (Yale University Press, 2013)
The Marquess of Queensberry is perhaps as famous for destroying one of our greatest literary geniuses as he was for helping establish the rules for modern-day boxing. The trial and two-year imprisonment of Oscar Wilde, following a series of events inspired by Wilde's romantic interest in his son, remains one of history's great tragedies. However, Linda Stratman's biography of the marquess, also known as John Sholto Douglas paints a far more complex picture by drawing on new sources and unpublished letters.